Quibas-Sima: A unique 1 ma-old vertebrate succession in southern Iberian Peninsula. (1st May 2022) - Piñero, Pedro; Agustí, Jordi; Laborda, Casto; Duval, Mathieu; Zhao, Jian-xin; Blain, Hugues-Alexandre; Furió, Marc; Laplana, César; Rosas, Antonio; Sevilla, Paloma
Abstract: With the identification of the Jaramillo geomagnetic subchron, the late Early Pleistocene vertebrate succession of the Quibas-Sima section (Quibas karstic complex, southern Spain) represents a time span scarcely recorded in Europe. To complete the existing chronostratigraphic framework published earlier by Piñero et al. (2020), we provide here additional new information about the lithostratigraphy and micromammal succession along the sedimentary sequence. Seven lithostratigraphic units have been differentiated (QS-1 to QS-7) at Quibas-Sima, documenting an almost continuous small mammal record, including representatives of the families Soricidae, Erinaceidae, Rhinolophidae, Vespertilionidae, Arvicolidae, Muridae, Gliridae, Sciuridae, Leporidae and Ochotonidae. The small mammal association indicates that units QS-1 to QS-4 have an intermediate biostratigraphic position between the sites of Fuente Nueva 3 (ca. 1.2 Ma) and Cueva Victoria (ca. 0.9 Ma). New numerical age result from the combined U-series/ESR dating of one equid tooth from QS-3 consistently support the general chronostratigraphic framework based on magnetostratigraphy and biostratigraphic inferences by confirming a post-Olduvai age. Based on an estimation of the sedimentation rate during the Jaramillo subchron, these broad chronological constraints may be confidently refined to approx. 1.1–0.9 Ma for the whole sequence. While we acknowledge the existing uncertainty associated to this age range, it is nevertheless consistent with biostratigraphic evidence indicating that all stratigraphic units most likely do not significantly differ from a chronological point of view. Both independent proxies (biostratigraphy and the sedimentation rate) strongly suggest that the sedimentary sequence covers a relatively short time interval (<200 kyr). These results place the Quibas-Sima sequence as one of the longest and most complete pre-Jaramillo (QS-1) to Jaramillo (QS-2 to QS-5) continental vertebrate succession in Europe. Highlights: Quibas-Sima is one of the very few palaeontological localities in Europe where the Jaramillo subchron has been identified. Information about the lithostratigraphy and micromammal succession along the Quibas-Sima sequence is provided. Numerical age result from the combined U-series/ESR dating support the general chronostratigraphic framework. Estimation of the sedimentation rate allows refining the chronological constraints to roughly 1.1–0.9 Ma for thesequence. Quibas-Sima is one of the longest and most complete pre-Jaramillo to Jaramillo continental vertebrate succession in Europe.